Thin-walled Ni-Ti tubes under compression: ideal candidates for efficient and fatigue-resistant elastocaloric cooling. (September 2020) - Porenta, Luka; Kabirifar, Parham; Žerovnik, Andrej; Čebron, Matjaž; Žužek, Borut; Dolenec, Matej; Brojan, Miha; Tušek, Jaka
Highlights: Buckling stability and fatigue life of thin-walled Ni-Ti tubes were studied Ni-Ti tubes withstood over a million full transformation compressive fatigue cycles Adiabatic temperature change of 27 K was measured after one million fatigue cycles This is the largest directly measured durable elastocaloric effect to date Thin-walled Ni-Ti tubes are ideal candidates for efficient elastocaloric devices Abstract: Elastocaloric cooling is emerging as one of the most promising alternatives to vapor-compression cooling technology. It is based on the elastocaloric effect (eCE) of shape memory alloys (SMAs), which occurs due to a stress-induced martensitic transformation (superelasticity). In recent years, several elastocaloric proof-of-concept devices have been developed and the best of them have already achieved commercially relevant cooling characteristics. However, the proposed devices are not yet ready for commercialization, mostly due to their short fatigue life, which is a consequence of the tensile loading. The fatigue life can be significantly improved if the material is instead subjected to compressive loading, but mechanical instabilities (buckling) and the poor heat transfer of bulky geometries (favorable for compression) are the major challenges to overcome when designing compressed elastocaloric elements. Here, we show for the first time that thin-walled Ni-Ti tubes, which allow for the rapid heat transfer, can withstand more than 10 6 compressive loading cycles without any degradation of the eCE while maintaining high efficiency (coefficient of performance) and adiabatic temperature changes as high as 27 K. This is the largest, directly measured, durable eCE for any elastocaloric material in the high-cycle fatigue regime to date, and so opens up new avenues in the development of durable and efficient elastocaloric devices. Graphical abstract: Image, graphical abstract